Choice of Management Specialisation Courses: Assessing the Role of Consideration of Prospects, and Individual and Social Factors - Shrestha, Shankar Kumar; Shrestha, Bikash (Journal of Business and Social Sciences Research, 2021)
This paper presents the results of a survey that examined the decision-making variables influencing the specialisation choice of undergraduate management students from a consumer behaviour perspective. Tribhuvan University has designed their undergraduate BBA programme by offering students the facility to customise their educational programme through the specialisation in four different areas: banking & finance, industry and services management, micro enterprise management, and sales and marketing management. Using the factorial ANCOVA research design and multistage sampling technique, 114 students from 10 out of 25 campuses, the study concludes that the past academic performance (individual factor) has the significant effect on selecting the specialisation courses among banking and finance, and marketing management. The effect of social factor and future prospect consideration have insignificant effect on SC after controlling the covariate individual factor (past academic performance). However, the significant interaction of SF_I and FPC_I in the full factorial model implies that there is at least effect of the intensities of SF and FPC on the specialisation course selection among the TU BBA students.